2020
DOI: 10.1353/hpu.2020.0025
|View full text |Cite
|
Sign up to set email alerts
|

Rental Assistance and Adult Self-Rated Health

Abstract: Rental assistance, in the form of vouchers and project-based subsidized housing, is a primary source of aff ordable housing for low-income Americans, given a growing and severe shortage of private-market rental units. However, due to supply constraints, fewer than one in four eligible households receive this kind of assistance. In this paper, we examine associations between receipt of rental assistance and self-rated health among a sample of 400 low-income adults in one U.S. city. We fi nd that individuals who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…Given that families who receive rental assistance tend to be an extremely disadvantaged subset of the U.S. population ( Foster and Rojas 2018 ; Helms et al 2017 ), greater investments in affordable and stable housing represent a valuable policy lever for reducing inequalities in child health. These results are consistent with other recent evidence suggesting that rental assistance provides a health benefit for both children and adults ( Boudreaux et al 2020 ; Fenelon et al 2018 ; Keene et al 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Given that families who receive rental assistance tend to be an extremely disadvantaged subset of the U.S. population ( Foster and Rojas 2018 ; Helms et al 2017 ), greater investments in affordable and stable housing represent a valuable policy lever for reducing inequalities in child health. These results are consistent with other recent evidence suggesting that rental assistance provides a health benefit for both children and adults ( Boudreaux et al 2020 ; Fenelon et al 2018 ; Keene et al 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moratoria are critical emergency measures to control the spread of COVID-19 and protect renters from eviction and associated harms, including the immediate risk of infection. With supportive legal and financial measures, such as rental assistance [105], eviction diversion programs [106], and civil right to counsel [107], states and localities are better able to protect vulnerable residents from eviction. Rental assistance programs can eliminate accumulated rental debt, reduce rent burdens, and increase housing stability, especially among low-income renters who have experienced COVID-19-related job or income loss [108].…”
Section: Supportive Measures May Aid In Prevention Of Eviction and Thmentioning
confidence: 99%
“…Further research into the health impacts and racial/ethnic disparities of COVID-19-related housing insecurity and the formulation of effective interventions and countermeasures to reduce housing insecurity effects on health outcomes, therefore, becomes critical. Research by Fenelon et al (2017) and Keene et al (2020) has indicated housing assistance is associated with improved reported health among low-income adults ( Lawler, 2001 ); and eviction moratoriums instated during the COVID-19 pandemic were also associated with better health among U.S. adults ( Leifheit et al, 2021 ). However, our research signals that, in the aftermath of acute economic events such as the current pandemic or economic recessions, these housing supports and benefits (i.e., more affordable housing, preventing insecurity in the first place) should be extended to midlife adults, particularly in Black communities, rather than only the elderly population to protect/preserve population health.…”
Section: Discussionmentioning
confidence: 99%